Water, energy & food sustainability in the Middle East : the sustainability triangle - Badran, Adnan; Murad, Sohail; Baydoun, Elias; Daghir, N. J. 1935- (Springer, 2017)
This book provides a survey of technologies available to tackle the problems associated with climate change in the energy, water and food security nexus with a special focus on the Middle East. It is divided into three main sections. The energy Section consists of six chapters, the water section of seven chapters and finally the food security section has six chapters. The individual chapters are authored by experts and provide discussions and in-depth views on the current status of each topic.
Keywords: Sustainability -- Middle East.; Water-supply -- Middle East.; Food supply -- Middle East.; Renewable energy sources -- Middle East.; Middle East.; elektronické knihy; electronic books